ADULT LEARNERS’ EXPERIENCES IN LEARNING ENGLISH: A CASE STUDY OF TWO UNIVERSITY STUDENTS IN INDONESIA - Yustinus Calvin Gai Mali (Center of Language and Cultural Studies [CLCS], 2017)
As a modified replication of Bellingham’s (2004) investigation, this case study primarily explores experiences of 30s Indonesian university students in learning English as a Foreign Language (EFL) at English Language Education Study Program, Masyarakat University Indonesia (ED-DU). The study specifically investigates cases of two ED-DU students who shared their experiences in learning EFL in their age. I recalled their experiences using an open-ended questionnaire and a semi-structured interview. I continued to collate and summarize the data into themes. Eventually, the present findings reveal six learning patterns of the students, confirm the existence of L2 acquisition for adult learners stated by Bellingham’s investigation, and provide some evidence that EFL learning acquisition is not limited by age.